2020
DOI: 10.1111/1365-2435.13707
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory underpins the nitrogen cycle

Abstract: 1. Tropical rainforests are populated by large frugivores that feed upon fruit-producing woody species, yet their role in regulating the cycle of globally important biogeochemical elements such as nitrogen is still unknown. This is particularly relevant because tropical forests play a prominent role in the nitrogen cycle and are becoming rapidly defaunated. Furthermore, frugivory is not considered in current plant-large herbivore-nutrient cycling frameworks exclusively focused on grazers and browsers. 2. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 68 publications
(126 reference statements)
2
48
0
1
Order By: Relevance
“…Villar et al (2020) observed strong evidence for impacts of frugivores on N cycling in their system. Overall, total N in soil was higher in the presence of frugivores than in the absence of these animals.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Villar et al (2020) observed strong evidence for impacts of frugivores on N cycling in their system. Overall, total N in soil was higher in the presence of frugivores than in the absence of these animals.…”
mentioning
confidence: 93%
“…Villar et al (2020) begin to fill the gap in frugivore zoogeochemistry with an experiment of ungulate frugivore effects on elemental cycling in the Atlantic Forest of Brazil. Specifically, the authors report on an 8‐year control‐exclusion (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies support a strong connection between rewilding as a restoration strategy and sustainable human development, noting that the promotion of rewilding in policy and decision-making would strongly support the post-2020 biodiversity goals (Perino et al 2019, Pereira et al 2020, Svenning 2020, Pasgaard et al Under revision). Trophic rewilding (Svenning et al 2016) recognizes the key role that megafauna species have on ecosystems processes, from seed dispersal, frugivory, herbivory and nutrient cycles (Pérez-Méndez et al 2016, Villar et al 2020, Enquist et al 2020)— to effects on fauna and flora communities (Galetti et al 2017), vegetation structure (Sandom et al 2014, Riesch et al 2020) and carbon storage (Bello et al 2015). The long-history of coevolution with extant species and the disproportionate impact they have on the environment (Enquist et al 2020) make megafauna species a potentially key element in our efforts to restore biodiverse and resilient ecosystems (Svenning et al 2016, Fernández et al 2017, Perino et al 2019, Schowanek et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, these edge effects have rarely been documented beyond a few hundred meters (10,14,15). Wildlife plays an important role moderating nutrients like nitrogen and phosphorus, and soil biota through deposition of excrement and carcases (16-19). Wildlife also affects soil physical environments through biopedoturbation (20-22) and plant-soil interactions via herbivory or nest building (23-26).…”
Section: Introductionmentioning
confidence: 99%